A Simple Mathematics Motivation Scale and Study of Validation in Mexican Adolescents. (March 2022) - Arellano-García, Yuridia; Vargas-De-León, Cruz; Guzmán-Martínez, María; Reyes-Carreto, Ramón
The goal of the study was to evaluate and adjust the model that associates mathematical motivation and learning strategies as quantitative instruments. The items related to the task value, cost, and self-efficacy were validated with Mexican students of rural areas in south-west region of Mexico between 12 and 16 years old, using 14 items that measure self-reported motivation levels. The construct validity of the mathematics motivation scale was checked using confirmatory factor analysis (CFA), by analyzing first- and second-order CFA models. The factor reliability was investigated by means of Dillon-Goldstein's rho and Cronbach's alpha. The model had adequate goodness of fit of in the confirmatory analysis. The instrument proved that it is convenient and reliable for application in mathematics motivation in Mexican adolescents. An advantage of the use of this instrument to be applied by teachers of mathematics is its simplicity, ease of application, and interpretation.